(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With the aim to discover new innovative antiinfective agents or to control multidrug resistant bacteria, a combinatorial library of some new heterocyclic derivatives pyrazoline (6a-e) and pyrimidine (7a-e) ring systems incorporate indole nucleous were designed and synthesised from chalcones. Chalcones (5a-e) react with hydrazine hydrate and guanidine hydrochloride gives 1-acetyl pyrazoline (6a-e) and 2-amino pyrimidine (7a-e) derivatives respectively. Confirmation of structures was assigned on the basis of FTIR, 1H NMR, 13C NMR spectral data as well as elemental analysis. In vitro antimicrobial as well as antitubercular proficiency of the title compounds were screened against selected pathogens. Compounds 5b, 5c, 5e, 6c, 7b and 7c exhibited excellent antimicrobial activity and said to be the most proficient members of the series.